(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Herein, we study the Hardy type inequalities using two-point right focal problem’s green functions that are convex for both variables involved along with the n−convex function. Furthermore, we analyze the aforementioned inequality by using Fink’s identity. In the later part, we gave Ostrowski type and Gr¨uss type inequalities by using the Cebyˇsev functional. Finally, we define ˇa functional obtained from our results that is employed to develop the mean value theorem and n-exponential convexity.